2014
DOI: 10.11114/jets.v3i1.573
|View full text |Cite
|
Sign up to set email alerts
|

STEM Faculty Experiences with Students with Disabilities at a Land Grant Institution

Abstract: Preparing faculty to meet the needs of the increasing number of students with disabilities is a critical need in higher education, particularly in the STEM (science, technology, engineering, and mathematics) fields. Quality preparation is an emerging problem as the number of higher education students with disabilities is on the rise. In this study, researchers used a qualitative methodology to examine STEM faculty members' experiences with students with disabilities at a land grant institution in the southeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 10 publications
(12 reference statements)
4
45
0
5
Order By: Relevance
“…This research has shown that insufficient experience and training in the field of disability was considered to be one of the main barriers to inclusivity in the university, as other studies (Lovet et al, 2015;Moswela & Mukhopadhyay, 2011) have confirmed. However, there are other contributing factors.…”
Section: Conclusion and Discussionsupporting
confidence: 55%
“…This research has shown that insufficient experience and training in the field of disability was considered to be one of the main barriers to inclusivity in the university, as other studies (Lovet et al, 2015;Moswela & Mukhopadhyay, 2011) have confirmed. However, there are other contributing factors.…”
Section: Conclusion and Discussionsupporting
confidence: 55%
“…Various authors discuss negative systemic issues faced by disabled students in higher education including accessibility, level of participation, stigmatization, lack of financial support, difficulty seeking accommodation [4,[51][52][53][54][55][56], lack of awareness of faculty and peers [51,55], identity of the disabled student [4,52,57], and career choice and development [58][59][60][61]. The Canadian organization, National Educational Association of Disabled Students (NEADS), produced a report in 2018 on the situation of Canadian graduate students with a disability [15] highlighting various problems faced by disabled graduate researchers.…”
Section: Role Identity and Career Developmentmentioning
confidence: 99%
“…We find this surprising and problematic. There are many problems disabled students encounter as part of their university experience: accessibility, stigmatization, lack of financial support, difficulty seeking accommodation, lack of awareness of faculty and peers, and the identity of the disabled student [4,[51][52][53][54][55][56][57][58][59][60][61]. Disabled graduate students indicated less satisfaction in all questions related to research experience than non-disabled graduate students in a 2018 study by the National Educational Association of Disabled Students (NEADS) [15].…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Por otro lado, las investigaciones evidencian que el profesorado no está formado en el uso de las metodologías pedagógicas más adecuadas para hacer frente a un aula diversa. En diferentes trabajos se plantea que el profesorado no está preparado para atender o dar respuesta a las necesidades de aprendizaje de estos estudiantes (Cardoso, 2013;Lovet et al, 2015;Moriña, Cortés y Molina, 2015;Moswela y Mukhopadhyay, 2011).…”
Section: Introductionunclassified